DESAIN PESAN PEMBELAJARAN BAGI SISWA PENDIDIKAN DASAR - Mustaji, (Pendidikan Dasar, 2010)
Abstracts: The characteristics of a message receiver should be identified before designing a learning message. It is related to the different possibilities of a message bulk and the chosen channel. Some characteristics necessarily identified are cognitive style, learning types, motivation achievement, development aspect, socio cultural aspect and demography. Finally it is also important to know that there is a new way of communication, i.e. horizontal versus vertical.